Anti-inflammatory Effect Of Myrtusnivelleibatt&trab (myrtaceae) Methanolic Extract - Touaibia, M.; Chaouch, F.z. (University of Eloued جامعة الوادي, 2015)
This work aims at evaluating the anti-inflammatory activity of an endemic species ofthe central sahara: MyrtusnivelleiBatt&Trab. The methanolic extract of this plant was extracted by Soxhlet apparatus and concentrated under reduced pressure using a rotary evaporator. In the carrageenan-induced paw edematest, five different groups of mice were established and the extract was administered orally in three different doses. The dose of 400 mg/kg was able to reduce significantly the paw edema with a comparable effect to that observed with Diclofenac (positive control).This is the first report to demonstrate a significant anti-inflammatory activity of the methanolic extract prepared from Myrtusnivellei.
Articale in Journal of fundamental and Applied Sciences Vol. 07 N. 01
Keywords: Anti-inflammatoy activity; MyrtusnivelleiBatt & Trab; methanolicextract; paw edema.